Moral Hazard in Agricultural Yield Insurance - Luo, Boyingzi (Archives of Business Research, 2020)
In agricultural yield insurance practices, there are two main categories of insurance products which differed from the targeted insured yield, namely area-yield based insurance and individual-based insurance. A common knowledge is that individual-yield based insurance has more flexibility that could meet the real demand of insureds, while having much more severity of moral hazard and higher administration costs. Relatively, area-yield based insurance has lower risk of moral hazard, but obtaining bias, or so-called basis risk at the same time. In this paper, we use an improved modified Miranda Decomposition Model to establish a theoretical framework of farmers behaviors when assuming their goals are to maximize the expected rate of return in agricultural production process under both individual-yield and area-yield insurance. The results show that these two distinct arrangements may cause different motivation to farmers, seducing them act or not act in moral hazard manner.